Pengaruh Citra Toko Terhadap Keputusan Pembelian Pada Loka Supermarket Malang - Lucky, Octhavian Sukmartha (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
The development of retail businesses in meeting the various preference for goods and services, has raised various forms of retail business/retail business (retail business). One form of retail business of large-scale modern privately run and continues to thrive is a department store. One strategy that can be applied in shaping consumer perceptions against a department store image strategy is through a shop/store image. The purpose of this research is to know the influence of the image of the store against the decision of the purchase at a local Supermarket was unfortunate. This research is explanatory research research. This research was conducted at the Loka Supermarket Malang. This research using a sample of as many as 100 consumer respondents Loka Supermarket. Hypothesis test is performed using a test t. data analysis using Multiple Linear regression analysis and SPSS software assisted by 20 to facilitate research. From the results of testing the hypothesis that has been done can be inferred that the variable image stores the positive effect against consumer purchasing decisions with Unfortunate Supermarket Loka indicator merchandise (product), promotion (promotion), comfort (convenience), on-site convenience store (store facilities) and service store (store service). Thus it takes special attention to formation of the image of the store in creating a good image or impression so that consumers have dared to do the purchasing decisions at retail. From hypothesis testing, obtained an influential shop facilities that most dominant against the purchasing decision.Keywords: Image Store, Stores Facilities, Purchasing Decisions